Deletion of Wntless in myeloid cells exacerbates liver fibrosis and the ductular reaction in chronic liver injury. Issue 1 (December 2015) - Irvine, Katharine; Clouston, Andrew; Gadd, Victoria; Miller, Gregory; Wong, Weng-Yew; Melino, Michelle; Maradana, Muralidhara; MacDonald, Kelli; Lang, Richard; Sweet, Matthew; Blumenthal, Antje; Powell, Elizabeth
Abstract Background Macrophages play critical roles in liver regeneration, fibrosis development and resolution. They are among the first responders to liver injury and are implicated in orchestrating the fibrogenic response via multiple mechanisms. Macrophages are also intimately associated with the activated hepatic progenitor cell (HPC) niche or ductular reaction that develops in parallel with fibrosis. Among the many macrophage-derived mediators implicated in liver disease progression, a key role for macrophage-derived Wnt proteins in driving pro-regenerative HPC activation towards a hepatocellular fate has been suggested. Wnt proteins, in general, however, have been associated with both pro- and anti-fibrogenic activities in the liver and other organs. We investigated the role of macrophage-derived Wnt proteins in fibrogenesis and HPC activation in murine models of chronic liver disease by conditionally deletingWntless expression, which encodes a chaperone essential for Wnt protein secretion, in LysM-Cre-expressing myeloid cells (LysM-Wls mice). Results Fibrosis and HPC activation were exacerbated in LysM-Wls mice compared to littermate controls, in the absence of an apparent increase in myofibroblast activation or interstitial collagen mRNA expression, in both the TAA and CDE models of chronic liver disease. IncreasedEpcam mRNA levels paralleled the increased HPC activation and more mature ductular reactions, in LysM-Wls mice. Increased Epcam expression in LysM-Wls HPC was also observed, consistent with a more cholangiocytic phenotype. No differences in the mRNA expression levels of key pro-inflammatory and pro-fibrotic cytokines or the macrophage-derived HPC mitogen, Tweak, were observed. LysM-Wls mice exhibited increased expression ofTimp1, encoding the key Mmp inhibitor Timp1 that blocks interstitial collagen degradation, and, in the TAA model, reduced expression of the anti-fibrotic matrix metalloproteinases, Mmp12 andMmp13, suggesting a role for macrophage-derived Wnt proteins in restraining fibrogenesis during ongoing liver injury. Conclusion In summary, these data suggest that macrophage-derived Wnt proteins possess anti-fibrogenic potential in chronic liver disease, which may be able to be manipulated for therapeutic benefit.